Confucianism: a short introduction - John .H. (Oxford, 2006)
Blending scholarship with an original approach, this new introduction to Confucianism is an informative and intriguing guide to China's ancient philosophical tradition. Against the backdrop of 17th century China, the book follows a Confucian couple, together with their family, friends and staff, through a typical day. The result offers a fascinating insight, not only into the intellectual and scholarly aspects of Confucianism, but also into the nature of belief, culture and society in a living philosophical tradition. The key topics covered include: the intellectual and social role of women; Confucianism, art and poetry; the relationship with the western world and western faiths. Capturing the full scope of an ancient tradition, this innovative, well-research and accessible text should be of interest to anyone interested in Confucianism, scholars, students and general readers alike
Keywords: China-Ancient philosophical tradation